A Collaborative Approach to Digital Fabrication: A Case Study for the Design and Production of Concrete 'Pop-up' Structures. (June 2015) - Vazquez, Alicia Nahmad; Jabi, Wassim
The research presented in this paper utilizes industrial robotic arms and new material technologies to model and explore a prototypical workflow for on-site robotic collaboration based on feedback loops. This workflow will ultimately allow for the construction of customized, free-form, on-site concrete structures without the need for complex formwork. The paper starts with an explanation of the relevance of collaborative robotics through history in the industry and in architecture. An argument is put forward for the need to move towards the development of collaborative processes based on feedback loops amongst the designer, the robot and the material, where they all inform each other continuously. This kind of process, with different degrees of autonomy and agency for each actor, is necessary for on-site deployment of robots. A test scenario is described using an innovative material named concrete canvas that exhibits hybrid soft fabric and rigid thin-shell tectonics. This research project illustrates the benefits of integrating information-embedded materials, mass-customization and feedback loops. Geometry scanning, parametric perforation pattern control, computational analysis and simulation, and robotic fabrication were integrated within a digital fabrication deployment scenario. The paper concludes with a detailed report of research findings and an outline for future work.